2018
DOI: 10.1186/s12871-018-0526-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hemodynamic goal-directed therapy to reduce the incidence of bone cement implantation syndrome in patients undergoing cemented hip arthroplasty – a randomized parallel-arm trial

Abstract: BackgroundThe bone cement implantation syndrome (BCIS) is a frequent and potentially disastrous intraoperative complication in patients undergoing cemented hip arthroplasty. Several risk factors have been identified, however randomized controlled trials to reduce the incidence of BCIS are still pending. We hypothesized that goal-directed hemodynamic therapy guided by esophageal Doppler monitoring (EDM) may reduce the incidence of BCIS in a randomized, controlled parallel-arm trial.MethodsAfter approval of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
0
8
0
8
Order By: Relevance
“…The total sample size was <100 participants for 33 studies (Bahlmann et al, 2019;Bisgaard et al, 2013a;Bisgaard et al, 2013b;Cecconi et al, 2011;Colantonio et al, 2015;El Sharkawy et al, 2013;Funk et al, 2015;Han et al, 2016;Jammer et al, 2015;Joosten et al, 2019;Kaufmann et al, 2018;Kim et al, 2018;Kumar et al, 2016;Lobo et al, 2000;Mayer et al, 2010;Mikor et al, 2015;Mythen & Webb, 1995;Peng et al, 2014;Reisinger et al, 2017;Scheeren et al, 2013;Senagore et al, 2009;Shoemaker et al, 1988;Sinclair et al, 1997;Ueno et al, 1998;Van der Linden et al, 2010;Venn et al, 2002;Weinberg et al, 2017;Weinberg et al, 2019;Wu et al, 2017;Yin et al, 2018;Zakhaleva et al, 2013;Zeng et al, 2014;Zhang et al, 2013) (50%) and the majority (77%) were conducted in a single centre setting (Bartha et al, 2013;Bender et al, 1997;Benes et al, 2010;Bisgaard et al, 2013a;Bisgaard et al, 2013b;Boyd et al, 1993;Cecconi et al, 2011;…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The total sample size was <100 participants for 33 studies (Bahlmann et al, 2019;Bisgaard et al, 2013a;Bisgaard et al, 2013b;Cecconi et al, 2011;Colantonio et al, 2015;El Sharkawy et al, 2013;Funk et al, 2015;Han et al, 2016;Jammer et al, 2015;Joosten et al, 2019;Kaufmann et al, 2018;Kim et al, 2018;Kumar et al, 2016;Lobo et al, 2000;Mayer et al, 2010;Mikor et al, 2015;Mythen & Webb, 1995;Peng et al, 2014;Reisinger et al, 2017;Scheeren et al, 2013;Senagore et al, 2009;Shoemaker et al, 1988;Sinclair et al, 1997;Ueno et al, 1998;Van der Linden et al, 2010;Venn et al, 2002;Weinberg et al, 2017;Weinberg et al, 2019;Wu et al, 2017;Yin et al, 2018;Zakhaleva et al, 2013;Zeng et al, 2014;Zhang et al, 2013) (50%) and the majority (77%) were conducted in a single centre setting (Bartha et al, 2013;Bender et al, 1997;Benes et al, 2010;Bisgaard et al, 2013a;Bisgaard et al, 2013b;Boyd et al, 1993;Cecconi et al, 2011;…”
Section: Resultsmentioning
confidence: 99%
“…In nine studies (14%), there was incomplete outcome data (El Sharkawy et al, 2013;Jammer et al, 2015;Pestana et al, 2014;Salzwedel et al, 2013;Scheeren et al, 2013;Stens et al, 2017;Zakhaleva et al, 2013;Zeng et al, 2014;Zhang et al, 2013). Sixty-one studies (92%) were identified as at low risk of selective reporting bias (Ackland et al, 2015;Bahlmann et al, 2019;Bartha et al, 2013;Bender et al, 1997;Benes et al, 2010;Bisgaard et al, 2013a;Bisgaard et al, 2013b;Boyd et al, 1993;Brandstrup et al, 2012;Calvo-Vecino et al, 2018;Cecconi et al, 2011;Colantonio et al, 2015;Correa-Gallego et al, 2015;Davies et al, 2019;Donati et al, 2007;Funk et al, 2015;Gan et al, 2002;Gerent et al, 2018;Goepfert et al, 2013;Gomez-Izquierdo et al, 2017;Jammer et al, 2010;Joosten et al, 2019;Kaufmann et al, 2017;Kaufmann et al, 2018;Kim et al, 2018;Kumar et al, 2016;Luo et al, 2017;Mayer et al, 2010;McKendry et al, 2004;McKenny et al, 2013;Mikor ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations